Development of Career Employee In STIKES RS Anwar Medika: Qualitative Descriptive Study In STIKES RS Anwar Medika - Elis Anita Farida; Tri Ratnawati; Amiartuti Kusmaningtyas (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2020)
The aim of this study is to analyzes the career development of STIKES RS ANWAR MEDIKA employees by formulating employee performance indexes based on organizational structure and main tasks and functions. The research method used was an explanatory research method, using questionnaire as data collection tool that was distributed to 67 employees at STIKES RS Anwar Medika. Data analysis in this study uses descriptivei analysis and multiplei linear regressioni analysis. The iresults of the multiplei linear regressioni analysis ishowed that simultaneously and partially the variablesi of Career Planning, Careeri Direction, and Implementation of Career Developmenti had a significanti effect on iEmployee Job Performance. Its indicatedi by the simultaneousi test results obtainedi significance ivalue F of 0,000 whichi is smalleri thani ? of 0.05 (0,000 <0.05). The significancei value is belowi 5% so that results in H1 decisionsi are acceptedi and Ho is irejected. Partial itest results for iCareer Planningi obtained a isignificance valuei of t of 0.001 whichi is smalleri than ? of 0.05 (0.001 <0.05) iand the ihighest icoefficient B of 0.346. Partiali test resultsi of Career Directioni variablesi have the greatesti significancei t 0.031. Partial itest results for the ivariable Career iDevelopment iImplementation has the t least significancei of 0,000.